Bacille Calmette-Guérin (BCG) vaccination at birth and antibody responses to childhood vaccines. A randomised clinical trial. Issue 16 (11th April 2017) - ,; Andersen, Andreas; Kjærgaard, Jesper; Thøstesen, Lisbeth Marianne; Pihl, Gitte Thybo; Hoffmann, Thomas; Kofoed, Poul-Erik; Aaby, Peter; Nissen, Thomas Nørrelykke; Birk, Nina Marie; Smits, Gaby; Jeppesen, Dorthe Lisbeth; et al.
Highlights: BCG has no overall effect on the antibody response to pentavalent vaccine. Effect of BCG on antibody levels may be modified by age of BCG vaccination. Girls had significantly higher antibody levels against Haemophilus influenza type b and pneumococcus than boys. Abstract: Introduction: BCG vaccination has been associated with beneficial non-specific effects on child health. Some immunological studies have reported heterologous effects of vaccines on antibody responses to heterologous vaccines. Within a randomised clinical trial of Bacille Calmette-Guérin (BCG) vaccination at birth, The Danish Calmette Study, we investigated the effect of BCG at birth on the antibody response to the three routine vaccines against DiTeKiPol/Act-Hib and Prevenar 13 in a subgroup of participants. Methods: Within 7 days after birth, children were randomised 1:1 to BCG vaccination or to the control group (no intervention). After three routine vaccinations given at age 3, 5 and 12 months, antibodies against DiTeKiPol/Act-Hib and Prevenar 13 ( Streptococcus pneumoniae serotype type 4, 6B, 9V, 14, 18C, 19F and 23F) were measured 4 weeks after the third vaccine dose. Results: Among the 300 included children (178 BCG; 122 controls), almost all children (>96%) had antibody responses above the protective levels. Overall BCG vaccination at birth did not affect the antibody level. When stratifying by 'age at randomisation' we found a possible inducing effect of BCG on antibodies against B. pertussis and all pneumococcal serotypes, when BCG was given after the first day of life. Girls had significantly higher antibody levels for Haemophilus influenza type b and pneumococcus than boys. Conclusions and relevance: Three routine vaccinations with DiTeKiPol/Act-Hib and Prevenar 13 induced sero-protective levels in almost all children. No overall effect of neonatal BCG vaccination was observed.